Factors driving carbon accumulation in forest biomass and soil organic carbon across natural forests and planted forests in China - Wang, Tao; Dong, Lingbo; Liu, Zhaogang (Frontiers in Forests and Global Change, 2024)
Introduction Forests play a pivotal role within the global carbon cycle. However, how to enhance carbon storage in existing forests remains unclear. Methods In this study, we conduct a comprehensive analysis of data from 2,948 forest sites across China. Utilizing structural equation modeling (SEM), we investigate the intricate relationship between climate, tree species diversity, stand structure, function traits, initial biomass carbon stocks (BCi), soil organic carbon stocks (Soil C content), and carbon accumulation in biomass (ΔBC) and soil organic carbon stocks (ΔSOC) within both natural forests (NF, n = 1,910) and planted forests (PF, n = 1,038). Results Our findings underscore the critical influence of tree species diversity and stand structure drivers of both direct and indirect carbon accumulation, with distinct drivers emerging based on the carbon pools in NF and PF. Specifically, increasing tree species diversity from its minimum to maximum value through management-results in a 14.798 tC/ha reduction in BC and 0.686 tC/ha in SOC in NF. Conversely, amplifies BC and SOC in PF by 0.338 tC/ha and 0.065 tC/ha, respectively. Enhancing stand structure-such as stand density-results in a 231.727 tC/ha reduction in BC and SOC in NF, and a 10.668 tC/ha in BC and 64.008 tC/ha increment in SOC in PF. Discussion Overall, our results indicate that higher tree species diversity, stand density and age-group limits further carbon accumulation in BC and SOC in current NF. In contrast, low tree species diversity and stand density limits the development of carbon storage potential in planted forests. To enhance carbon sequestration capacity, China should change its current policy of completely banning logging of natural forests. Natural forests need thinning and reduced tree species diversity, while planted forests should increase tree species diversity and stand density.